Skeletal and dental changes induced by bionator in early treatment of class II - Dirceu Barnabé Raveli; João Paulo Schwartz; Taísa Boamorte Raveli; Ary dos Santos Pinto; Bryan Tompson (Acta Scientiarum. Health Sciences, 2016)
The purpose was to investigate the amount of skeletal and dentoalveolar changes after early treatment of Class II, Division 1 malocclusion with bionator appliance in prepubertal growing patients. Forty Class II patients were divided in two groups. Treated group consisted of 20 subjects treated consecutively with bionator. Mean age at the start of treatment (T0) was 9.1 years, while it was 10.6 years at the end of treatment (T1). Mean treatment time was 17.7 months. Pretreatment and post-treatment cephalometric records of treated group were evaluated and compared with a control group consisted of 20 patients with untreated Class II malocclusion. Intergroup comparisons were performed using Student’s t-tests and chi-square test with Yates’ correction at a significance level of 5 per cent. Bionator appliance was effective in generating differential growth between the jaws. Cephalometric skeletal measurements ANB, WITS, Lafh, Co-A and dental L6-Mp, U1.Pp, IsIi, OB, OJ showed statistically significantly different from the control. Bionator induced more dentoalveolar changes than skeletal during treatment in prepubertal stage.